Irritable bowel syndrome: pathophysiological and clinical issues - V. T. Ivashkin; Ye. A. Poluektova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of review. To discuss the issues of etiology, pathogenesis, clinical presentation and differential diagnostics of irritable bowel syndrome (IBS).Summary. At irritable bowel syndrome there are series of structural changes interconnected with each other, built into logic chain, that ends by development of symptoms. However it remains not quite clear, whether they determine severity and origin of clinical symptoms, as well as the degree of involvement of each of the basic known pathogenic mechanisms in development of symptoms in given patient is insufficiently clear. The long-term analysis of IBS symptoms has not led to development of clear diagnostic criteria due to both objective causes (frequent, up to 87% combination of various functional disorders) and due to possible identity of complaints in patients to IBS, clostridial infection, microscopic colitis, celiac sprue. Lack of scrutiny of etiology, pathogenesis, clinical presentation determines low treatment efficacy of such patients.Conclusion. Treatment of patients will allow to optimize further investigations of certain etiological, pathogenic factors, to carry out differential diagnostics of IBS more clearly.